Independence of The Honorary Board of Election Organizers After The Constitutional Court Decision No. 32/PUU-XIX/2021 - Ulya, Zaki; Fuadi, Fuadi; Putra, Aldi Syah (JURNAL USM LAW REVIEW, 2024)
This study aims to find out what the independence and integrity of the Honorary Board of Election Organisers (DKPP) are after the enactment of Constitutional Court Decision No. 32/PUU-XIX/2021. After the enactment of the Constitutional Court Decision No. 32/PUU-XIX/2021, DKPP experienced problems related to its independence, including limited authority, lack of independent supervisory functions, and rampant political intervention. All of these problems affect DKPP's role in carrying out its duties as a supervisor of election administrators. It is crucial to keep in mind that even with the changes in the DKPP's jurisdiction following the Constitutional Court's ruling, the organization's responsibility as a defender of morality and integrity in election administration is still crucial to maintaining a free, transparent, and democratic electoral process. This research uses normative juridical research methods, with a library research approach. To obtain secondary data related to this title so that valid and accountable data can be obtained, the approach used in this research is the statute approach. The findings of this research support the decision of the Constitutional Court No. 32/PUU-XIX/2023 which cancelled Article 458 paragraph (13) of Law No. 7/2017. This makes the decision of the Election Organiser Honour Council legally binding as a concrete, unique, and final decision made by a state administrative official, which can be challenged in the state administrative court. This decision has legal consequences because it confirms the final and binding nature of the Election Organiser Honour Council, which distinguishes it from judicial decisions; and opens up the possibility of testing the decision of the DKPP through the State Administrative Dispute procedure at the State Administrative Court.